PRICE COMPETITION OF IMPORTED CLOTHING PRODUCTS AND THRIFTING ON THE MARKET SHARE OF THE DOMESTIC GARMENT INDUSTRY IN CENTRAL JAVA - Wahyu Jumiarsih; Novita Putriyani; Septa Safeina Maris; Bangkit Suasono (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Price competition in the fashion industry is increasingly intensifying as the penetration of low-priced imported clothing products increases and the phenomenon of thrifting (imported used clothing) is rampant. This condition puts significant pressure on the sustainability of the domestic garment industry's market share, especially in Central Java as one of the national garment production centers. This study aims to analyze the influence of the price of new imported clothing and the price of used thrifting clothing on the market share of the domestic garment industry in Central Java, as well as examine the role of consumer interest as a mediating variable. This study uses a quantitative approach with primary data obtained through a questionnaire of 58 garment and convection business actors in Central Java. Data analysis was carried out using multiple linear regression and path analysis. The results of the study show that the price of new imported clothes and the price of used thrifting clothes have a positive and significant effect on the market share, both partially and simultaneously. In addition, consumer interest has been proven to be able to mediate the effect of the price of used thrifting clothes on market share, but does not mediate the influence of the price of new imported clothes. These findings indicate that consumer decisions on thrifting products are more influenced by interest and value perceptions, while decisions on new imported clothing are more rational and directly influenced by price. This research makes a theoretical contribution to the study of industrial competition and market crowding-out, as well as practical implications for business actors and policymakers in formulating strategies to strengthen the domestic garment industry.